2015
DOI: 10.3892/etm.2015.2638
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of 5-aminolevulinic acid photodynamic therapy in the treatment of moderate to severe facial acne vulgaris

Abstract: Abstract. Acne vulgaris is considered as a therapeutic challenge in terms of managing ongoing symptoms and preventing scar formation. Although there are many available treatments for alleviating acne, therapies for resistant or moderate-to-severe forms have been limited to systemic agents that are accompanied by potentially severe side-effects. While, aminolevulinic acid (ALA) photodynamic therapy (PDT) has increasingly been used as a simple and safe therapeutic option of acne vulgaris, the clinical efficacy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…However, cell therapy using ASCs is preferred because these cells are easy to isolate and have high relative abundance than BM-MSCs [9]. Moreover, studies suggest that transplanted ASCs accelerate wound healing by expanding the fibroblasts phenotype and increasing the supply of macrophages to the wound, enhancing granulation tissue formation [10][11][12]. Further studies showed that ASCs promote the growth of dermal fibroblasts through not only intercellular cell-to-cell contact, but also by paracrine activation of marginal cells [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, cell therapy using ASCs is preferred because these cells are easy to isolate and have high relative abundance than BM-MSCs [9]. Moreover, studies suggest that transplanted ASCs accelerate wound healing by expanding the fibroblasts phenotype and increasing the supply of macrophages to the wound, enhancing granulation tissue formation [10][11][12]. Further studies showed that ASCs promote the growth of dermal fibroblasts through not only intercellular cell-to-cell contact, but also by paracrine activation of marginal cells [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, almost 16 years have passed since the first studies on ALA-PDT in acne therapy; there is still no consensus on how to perform PDT for acne treatment, and its use still remains an off-label option for acne patients [22] . Despite numerous studies on PDT in acne (mainly mild to severe acne on the face but also acne lesions on the back and acne conglobata) [1,18,20,21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] ( Table 1 ), they are generally difficult to compare because of the lack of controls, qualitative non-blinded methods, variable light dosimetry, and an extremely wide variation of the incubation time between drug application and light exposure. All these differences should not be neglected.…”
Section: Acnementioning
confidence: 99%
“…Reports continued to appear describing ALA PDT with IPL, [123][124][125] the pulsed dye laser, 122,126 the KTP laser, 127 intralesional ALA, 128 MAL photosensitizer, [129][130][131][132][133][134][135] and newer photosensitizers. [136][137][138][139] ALA PDT has also been used to treat Asian, 124,140,141 Korean, 142 Japanese, 115,116,143 African-American, 144 and Chinese [145][146][147] patients.…”
Section: Evolution Of Pdtmentioning
confidence: 99%
“…Reports continued to appear describing ALA PDT with IPL, the pulsed dye laser, the KTP laser, intralesional ALA, MAL photosensitizer, and newer photosensitizers . ALA PDT has also been used to treat Asian, Korean, Japanese, African‐American, and Chinese patients.…”
Section: Photodynamic Therapymentioning
confidence: 99%